2010
DOI: 10.1172/jci37873
|View full text |Cite
|
Sign up to set email alerts
|

NFAT/Fas signaling mediates the neuronal apoptosis and motor side effects of GSK-3 inhibition in a mouse model of lithium therapy

Abstract: Use of lithium, the mainstay for treatment of bipolar disorder, is limited by its frequent neurological side effects and its risk for overdose-induced toxicity. Recently, lithium has also been proposed as a treatment for Alzheimer disease and other neurodegenerative conditions, but clinical trials have been hampered by its prominent side effects in the elderly. The mechanisms underlying both the positive and negative effects of lithium are not fully known. Lithium inhibits glycogen synthase kinase-3 (GSK-3) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 85 publications
(107 reference statements)
5
88
1
Order By: Relevance
“…66,77,88,11,15 Unexpectedly, we found that lithium treatment at doses inducing blood levels well below the human therapeutic range caused cognitive impairment and brain atrophy in mice after 3 weeks (Figures 4j-l). It has been shown previously that lithium treatment at therapeutic doses can cause cortical neuronal apoptosis, 17 and this may explain our findings. Although lithium treatment was previously reported to correct the smaller hippocampal volumes in patients with bipolar disorder, 85 there is also evidence that long-term lithium treatment is associated with cognitive impairment 86, 87, 88, 89 and brain atrophy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…66,77,88,11,15 Unexpectedly, we found that lithium treatment at doses inducing blood levels well below the human therapeutic range caused cognitive impairment and brain atrophy in mice after 3 weeks (Figures 4j-l). It has been shown previously that lithium treatment at therapeutic doses can cause cortical neuronal apoptosis, 17 and this may explain our findings. Although lithium treatment was previously reported to correct the smaller hippocampal volumes in patients with bipolar disorder, 85 there is also evidence that long-term lithium treatment is associated with cognitive impairment 86, 87, 88, 89 and brain atrophy.…”
Section: Discussionsupporting
confidence: 82%
“…This is probably because the tau-knockout mice in youth have the benefit of upregulated compensatory responses from other microtubule-associated proteins 45 in contrast to the more acute suppression of tau expression by lithium treatment. Our findings add to the evidence that lithium at therapeutic (and eventually even at subtherapeutic) chronic doses can cause neurodegeneration, 17 and provide a possible mechanism for adverse neurological effects in susceptible individuals.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Notably, the nuclear factor of activated T cell (NFAT) transcription factors have an important role in the development of the nervous system 7,8 and in the control of the survival/death fate of neurons. [9][10][11][12][13][14] The NFAT family comprises four calcium/calcineurindependent transcription factors that are encoded by four closely related genes. [15][16][17] NFAT proteins are expressed in most mammalian tissues, with the different members of the family being present in distinct but overlapping sets of cell types.…”
mentioning
confidence: 99%
“…Both NFATc3 and NFATc4 have been shown to have either proapoptotic or antiapoptotic effects, depending on the physiologic and cellular context. [9][10][11][12][13][14][20][21][22] However, the mechanisms that regulate their activity in response to apoptotic stimuli and the target genes that mediate their differential effects on neuronal apoptosis are mostly unknown.…”
mentioning
confidence: 99%